Impact of Improved Vegetable Technologies in Disadvantaged Districts of Uttar Pradesh - Singh, Neeraj; Roy, Shubhadeep; Singh, B.; Rai, A.B. (Indian Journal of Extension Education, 2015)
Mirzapur and Sonbhadra, two disadvantaged districts in Uttar Pradesh, were the target area under the NAIP sub project  component-3 during 2008-14. Both these districts are situated far south-east region of U.P. in the Vindhyan mountain  range. The baseline survey made during 2008-09 in the selected districts clearly indicated the lack of efficient agricultural  technology in the region and economic gap among the farmers. Intervention of various high yielding varieties along with  improved production and protection technologies in different vegetable crops not only increased the average productivity  of the crops from 2.48 to 27.54 per cent but also enhanced the average annual income of the households. The increased  productivity of vegetables has resulted in enhanced net return of ` 10298 to ` 34703 per hectare and the average annual  income of commercial vegetable growers was recorded as ` 59,695/- per household per year which is an improvement of  50.7 per cent per household per year.
Keywords: Disadvantaged district; improved vegetable varieties; productivity; farm income; impact